Induksi dan Karakter Pertumbuhan Kalus Triploid dari Endosperma Avokad (Persea americana Mill.) - Edy Sukmara; Lazarus Agus Sukamto; Maria Bintang (IPB University, 2014)
The concentration of the Plant Growth Regulators (PGR) medium as well as endosperm viability determines the success of triploid avocado callus. This study was aimed to explore the best size of diameter fruit and the most responsive concentration for the induction of endosperm avocado callus. The study consisted of two phases. The first stage is to determine the best diameter size of avocado and concentration of the culture medium that gave the fastest response to be endosperm callus. The second stage used flow cytometer to obtain triploid of avocado endosperm callus. This study used four size of fruit group diameter, that A=(0.30-0.50), B=(0.51-1.00), C=(1.01-1.50) and D=(1.51-2.20) in cm. Factorial experiment with four replications was arranged in a completely randomized design. Murashige and Skoog medium (MS) was used in this culture with two PGR that the Picloram and 2.4-D. Each with concentration : 0.5, 1.0, 2.0 and 4.0 in mg/l. The most responsive diameter fruit size was group B (0.30 – 0.50 cm) with the fastest callus growth average was 7.67 weeks after culture (WAC). The most responsive concentration for endosperm callus induction was Picloram 2 mg/l, growth in 5.08 WAC. The endosperm callus growth successfully t done by the inclusion of avocados embryos. The best interaction between fruits diameter and concentration for callus avocado induction used fruits diameter A with picloram 2 mg/l. The endosperm callus were measured by using flow cytometer resulted in avocado triploid callus with region range (RN) Mean value wer 302.01, 296.60, and 298.51 respectively. While the avocado leaf control resulted in 198.82 diploid plant.